Development of STEM-Based Student Worksheets through a Fly Repellent Project to Foster Students' Creative Thinking - Elvina, Defi; Saminan, Saminan; Evendi, Evendi (Universitas Muhammadiyah Makassar, 2025)
Creative thinking is one of the key competencies needed in twenty-first-century physics education. Yet, many classrooms still rely on traditional, teacher-centered instruction that leaves little space for student creativity or real-world application. At SMAN 4 Langsa, observations revealed that students often struggled to connect physics concepts with practical problems, underscoring the need for more context-based learning approaches. This study aimed to develop and evaluate STEM-based student worksheets centered on a fly repellent project to engage students in creative and applied problem-solving. Using a Research and Development (R&D) design guided by the ADDIE model Analysis, Design, Development, Implementation, and Evaluation the study involved 24 tenth-grade students. Data were gathered through expert validation, creative thinking tests administered before and after implementation, classroom observations, and response questionnaires. The worksheets were judged highly valid, with an average expert score of 90.5%, and proved effective in improving students’ creative thinking skills, with an average N-Gain score of 0.73, categorized as high. Significant progress was seen across all four indicators of creative thinking: fluency, flexibility, originality, and elaboration. Student responses indicated that 87% found the worksheets engaging and useful in linking physics concepts to real-life issues, while teachers valued them as innovative and effective learning tools. The novelty of this research lies in embedding an environmental health problem into physics learning, providing students with a meaningful context in which to apply their knowledge. These findings highlight the potential of STEM-based, project-oriented worksheets to make physics learning more relevant, engaging, and effective in fostering twenty-first-century skills.